The effect of quartet play on knowledge, attitude, and hand washing practices in school-aged children - Ria Kustiani; Umi Solikhah (UM Purwokerto Press, 2020)
Hand washing compliance is still relatively low. Efforts are needed to improve the quality of health and welfare, one of which is through education on the habit of hand washing with soap (HWWS). The objective of the study was to investigate the effect of play therapy using quartet media on knowledge, attitudes and practices of hand washing in school-aged children aged 9-12 years. This study employed a quasi-experimental one group pre-test-post-test method conducted at Banyumas Hospital. The sampling technique used was simple random sampling with a sample of 55 respondents. The research instruments occupied were a knowledge questionnaire, an attitude questionnaire, and an observation sheet for the practice of washing hands with soap. Data were analysed using the Wilcoxon test. The results revealed that knowledge, attitudes, and practices of washing hands with soap increased after being given play therapy using a quartet. The Wilcoxon test result obtained was a significance value (p) on the effect of playing therapy using quartet media, namely knowledge p = 0.000, attitude p = 0.000, and practice p = 0.000. Play therapy using quartet media has a significant influence on knowledge, attitudes, and practices of washing hands with soap.